Supressão do Campo Eléctrico Atmosférico aquando do sismo de Sousel, M = 4.1 - Silva, Hugo (2011)
In recent years different phenomena associated with seismic events have been referred in the literature. These include: unusual ultra-low-frequency electromagnetic emissions; anomalies in radio transmissions; variation of the ionosphere total electron content; and anomalous levels of different geochemical elements (in particular radon) in the earthquake preparation zone. Recent works shown the possibility of enhanced air ionization, with consequent atmospheric electricity perturbations, in the preparatory stage of seismic events. They relate possible atmospheric electrical field anomalies during the earthquake preparation with surface air ionization through radon emanations. In fact, this work presents the observation of a significant suppression of the vertical component of the atmospheric electrical field that occurred in Évora (Portugal) soon before the M = 4.1 Sousel earthquake of 27 March 2010. The observation is reported, followed by the analysis and interpretation. Preliminary conclusions and plans for future works are drawn.